Donor Nerve Selection in Facial Reanimation Surgery - Klebuc, Michael (Thieme Medical Publishers, 2004)
The motor components of local cranial nerves provide a series of options for the surgical rehabilitation of the paralyzed face. Nerve donor sites vary with respect to their motor power, functional deficit, and synergy with facial expression. A thorough understanding of each donor nerve's strengths and weaknesses facilitates the selection process. Technical modifications to reduce donor site morbidity and the emerging role of the masseter nerve are examined.